Ngapak E-Book Development: Text Material Description of Tourist Attractions for Grade VII of Junior High School - Tabita Hasna Nasifa; Nur Hanifah Insani (Institut Agama Islam Negeri Palopo, 2025)
This research is the development of teaching materials into Ngapak Wisata E-book. Based on the results of research that has been carried out, students and language teachers at SMP Negeri 1 Kaligondang need ebook ngapak teaching materials as teaching materials. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evalution). The purpose of this research is to develop teaching materials for e-books in ngapak language with descriptive text material. The subjects of this study were 28 students of class VII C of SMP Negeri 1 Kaligondang and Javanese language teachers of SMP Negeri 1 Kaligondang. The feasibility testing of this product was conducted by media experts and material experts.Testing the feasibility of this product was carried out by media experts and material experts. Data collection techniques using interviews and questionnaires. Data analysis used qualitative data obtained from converting scores into percentages of media and material validators. Data is used for guidelines in product evaluation. Quantitative data obtained descriptions of products developed. The results of the media expert assessment were 82.2% with the category